1
$\begingroup$

How to convert this integral into Beta Gamma function?

Any hints will be appreciated. $$\int_0^{b} x \sqrt{b^3-x^3} dx$$ Thanks

$\endgroup$
  • $\begingroup$ it is $$\frac{\sqrt{\pi } b^{7/2} \Gamma \left(\frac{2}{3}\right)}{6 \Gamma \left(\frac{13}{6}\right)}$$ for $\Re(b)>0$ and $\Im(b)=0$ $\endgroup$ – Dr. Sonnhard Graubner Oct 4 '17 at 8:38
  • $\begingroup$ How to get to this? $\endgroup$ – User Oct 4 '17 at 8:45
  • $\begingroup$ @User. Using magic, you get it ! $\endgroup$ – Claude Leibovici Oct 4 '17 at 8:58
1
$\begingroup$
  • notice that a change of variable $x=by$ will pull $b$ out of the integral (both integrand and bounds).

  • then notice that the change of variable $z=y^3$ will let the binomial $1-z$ appear under the radical, while other factor(s) will be powers of $y$, directly leading to a Beta integral.

$$\int _0^b x\sqrt{b^3-x^3}dx=b^{7/2}\int _0^1 y\sqrt{1-y^3} dy=\frac13b^{7/2}\int _0^1 z^{-1/3}\sqrt{1-z}\, dz.$$

$\endgroup$
2
$\begingroup$

Set $x =bt$ so that, $dx =bdt$ $$I:=\int_0^{b} x \sqrt{b^3-x^3} dx = \int_0^{1} b^2t \sqrt{b^3-b^3t^3} dt = b^{7/2}\int_0^{1} t (1-t^3)^{1/2} dt$$ Setting $u=t^3~~$ i.e $~~t= u^{1/3}~~$ yields $dt =\frac{1}{3}u^{-2/3}du~~~$ therefore,

$$I= b^{7/2}\int_0^{1} t (1-t^3)^{1/2} dt = \frac{1}{3}b^{7/2}\int_0^{1} u^{-1/3} (1-u)^{1/2} du\\=\frac{1}{3}b^{7/2}\int_0^{1} u^{2/3-1} (1-u)^{3/2-1} du\\=\frac{1}{3}b^{7/2} B\left(\frac{2}{3},\frac{3}{2}\right)$$

But

$$B\left(\frac{2}{3},\frac{3}{2}\right) = \frac{\Gamma\left(\frac{2}{3}\right)\Gamma\left(\frac{3}{2}\right)}{\Gamma\left(\frac{2}{3}+\frac{3}{2}\right)} =\frac{\Gamma\left(\frac{2}{3}\right)\Gamma\left(1+\frac{1}{2}\right)}{\Gamma\left(2+\frac{1}{6}\right)}=\frac{\frac{1}{2}\Gamma\left(\frac{2}{3}\right)\Gamma\left(\frac{1}{2}\right)}{(1+\frac{1}{6})\frac{1}{6}\Gamma\left(\frac{1}{6}\right)}\\= \color{red}{\sqrt{\pi}}\frac{18}{7}\frac{\Gamma\left(\frac{2}{3}\right)}{\Gamma\left(\frac{1}{6}\right)}$$ Since$$\Gamma\left(\frac{1}{2}\right) =\sqrt{\pi}$$

Conclusion $$\color{blue}{\int_0^{b} x \sqrt{b^3-x^3} dx =\color{red}{\sqrt{\pi}}b^{\frac{7}{2}}\frac{6}{7}\frac{\Gamma\left(\frac{2}{3}\right)}{\Gamma\left(\frac{1}{6}\right)} }$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.